Theory of Planned Behavior in AnalyzingThe decision of Muslim consumers to become members of 212 Mart Pekanbaru City - Sidabalok, Supriani; Rosyetti, Rosyetti; Zamaya, Yelly; Misdawita, Misdawita (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2023)
212 Mart Pekanbaru is one of the sharia retail businesses whose presence is expected to be able to provide a comfortable modern shopping place for Muslim consumers, especially in the city of Pekanbaru. Its relatively new presence causes it to not be able to compete and seize the existing market. Consumers themselves have several considerations in choosing a place to shop or become loyal consumers by joining as a member at a Mart. These reasons and considerations are important to analyze as input for Mart managers in managing their retail. By using Theory of Planned Behavior (TPB) as a theoretical basis, this research uses five independent variables namely income, attitude, subjective norms, individual control, and religiosity to see the main factors that influence consumer decisions to become members of 212 Mart. The analysis technique used in this study is logistic regression analysis with 100 consumers at 212 Mart Pekanbaru as respondents. The results showed that only the subjective norm variable had a significant effect on the Muslim consumer's decision to become a member of 212 Mart. The income, attitude, individual control, and religiosity variables have no significant effect.